The Impact of Emotional Intelligence and Job Involvement on Project Team Member’s Performance - Abubakr Ali Abdu Yosr Yaquot; Mohammed Abdulrahman Abdullah Al-Ghaili; Abdulrahman Ali Mohsen Al-Harethi (IPB University, 2021)
This study concentrated on job employee performance by using emotional intelligence, job involvement, leaders‘ trust, and job satisfaction. The researchers examined the job involvement and emotional inelegance factors on IT projects team member’s performance in China with the effect of moderator factor trust of leader and mediator impact job satisfaction. After reviewing many works of literature, the student explained and discussed the development of the hypothesis of emotional intelligence, Job involvement, the trust of a leader, and Job satisfaction with members‘ performance. This study has been conducted in Chinese projects, so the data was collected from IT projects members and workers who have been or still doing these kinds of projects using several ways to reach around 200 respondents as the online survey and social media. Using a different method and tests we could find that these relationships in the study were significant with positive impact except the moderation impact of trust leader. This study contributed to benefited IT, project leaders, and members, for better understanding especially for the importance of the emotional intelligence and job involvement for better performance of the team members which will also contribute to improving the IT project in China and will open new and different topics for researchers.